2015
DOI: 10.1021/ma502550f
|View full text |Cite
|
Sign up to set email alerts
|

Proton Dissociation of Sulfonated Polysulfones: Influence of Molecular Structure and Conformation

Abstract: The counterion condensation behavior of proton conducting sulfonated polysulfones has been investigated by combining electrophoretic NMR, pulsed magnetic field gradient NMR, and conductivity measurements on monomeric and polymeric samples with concentrations of ionic groups in the range where dissociation is not complete (IEC = 4.55–7.04 mequiv g–1). In this regime, counterion condensation is shown to critically depend on details of the molecular structure, and all atom molecular dynamics (MD) simulations reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…To facilitate phase separation, QA groups have been highly concentrated to segments in statistical and block copolymers . However, this strategy may lead to limitations in ion‐dissociation, and thus conductivity, caused by the close proximity of the ions in the polymer structure …”
Section: Preparation Conductivity and Degradation Of Aemsmentioning
confidence: 99%
“…To facilitate phase separation, QA groups have been highly concentrated to segments in statistical and block copolymers . However, this strategy may lead to limitations in ion‐dissociation, and thus conductivity, caused by the close proximity of the ions in the polymer structure …”
Section: Preparation Conductivity and Degradation Of Aemsmentioning
confidence: 99%
“…showed that an increase in the IEC (decreasing the average separation distance of sulfonic acid groups) leads to improved proton conductivity. However, this improvement is limited to how close the sulfonic acid groups are to each other to conform to a stable triple ion aggregate (Figure ) thereby lowering conductivity and leading to a minima in free energy (Δ F ) …”
Section: Resultsmentioning
confidence: 99%
“…23 Dissipative particle dynamics (DPD) simulations have shown that the sPSO 2 -220's polyelectrolyte backbone is significantly stiffer as for example the polyethylene backbones of PAMPS or PSS. 24,25 Furthermore, due to the electron withdrawing sulfonyl group (-SO 2 -) the sulfonate group is especially acidic for sPSO 2 -220, which leads to high dissociation degrees of 54-61%, 26,27 in comparison to a dissociation degree of 33-38% for PSS or PAMPS. 28,29 C 14 TAB was chosen as surfactant, as it is the shortest surfactant in the C n TAB series that forms stable films on its own.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the composition, the homogeneity and the structure of the film will be investigated in a further publication using neutron reflectometry (NR). Secondly, the higher dissociation degree of sPSO 2 -220 as of PAMPS, 27 leads to higher ionic strength, which in turn leads to higher surface potentials. The difference in surface potential C 0 also helps to explain the higher foam film stability of sPSO 2 -220/C 14 TAB mixtures in comparison to PAMPS/C 14 TAB mixtures, as higher surface potential leads to more stable foam films.…”
mentioning
confidence: 99%